Assessment of Monitoring and Evaluation of Capital Projects in Hadiya Zone, South Ethiopia - Mekoro Arega Gashe (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
This study was conducted to assess the factors affecting monitoring and evaluation of capital projects in selected woredas of Hadiya Zone, south Ethiopia. The main sources of data were both primary and secondary sources of data. Primary data were collected through questionnaires administered to the selected respondents and interview. The sampling technique employed for this research was purposive sampling to select sample Woredas. The binary logistic regression analysis was used by applying stata 14 software. Results of the study revealed that there is a positive and significant relationship between effective monitoring and evaluation of governmental capital project and availability of budget. Regression analysis revealed that a unit change in availability of budget increased evaluation of capital projects in government organization 1.409 units. Correlation analysis showed that there was a positive and significant relationship between stakeholder participations and evaluation of capital projects in government organization. Regression analysis revealed that a unit change in stakeholder participations increases effectiveness of evaluation of capital projects by 1.192 units. The study revealed that there was a positive and significant relationship between selection tools and techniques or methods and evaluation of capital projects. Regression analysis showed that a unit change in selection tools and techniques/methods increased monitoring and evaluation of capital projects by 2.721 units. Regression analysis showed that a unit change in skill level of experts increased effectiveness of monitoring and evaluation of capital projects by 2.688 units. The skill level of experts significantly affects the capital projects performance of monitoring and evaluation system. The planning, monitoring and evaluation core work process of governmental organization’s capital projects in each sector should employ experienced and skilled human power so that they can put in place effective monitoring and evaluation system.